Learning Arabic in Renaissance Europe (1505-1624) - Jones, John Robert, 1952- (The History of Oriental Studies;, 2020)
"From the first Arabic grammar printed at Granada in 1505 to the Arabic editions of the Dutch scholar Thomas Erpenius (d.1624), some audacious scholars - supported by powerful patrons and inspired by several of the greatest minds of the Renaissance - introduced, for the first time, the study of Arabic language and letters to centres of learning across Europe. These pioneers formed collections of Arabic manuscripts, met Arabic-speaking visitors, studied and adapted the Islamic grammatical tradition, and printed editions of Arabic texts - most strikingly in the magnificent books published by the Medici Oriental Press at Rome in the 1590s. Robert Jones' findings in the libraries of Florence, Leiden, Paris and Vienna, and his contribution to the history of grammar, are of enduring importance".